Compartment Syndrome in Tibial Plateau Fractures: Do Previously Established Predictors Have External Validity?. Issue 5 (May 2020) - Marchand, Lucas S.; Working, Zachary M.; Rane, Ajinkya A.; Elliott, Iain S.; Gilbertson, Ellen; Rothberg, David L.; Higgins, Thomas F.; Haller, Justin M.
Abstract : Objective: To test previously established radiographic predictors of compartment syndrome in tibial plateau fractures and determine whether novel measurements may further improve a surgeon's ability to identity patients at high risk for developing this outcome. Design: Retrospective review. Setting: Academic Level I trauma center. Patients: Five hundred thirteen patients with tibial plateau fractures treated operatively over a 10-year period (OTA/AO 41B1-3 & 41C1-3; Schatzker I-VI). Intervention: Previously established plain film radiographic measurements and novel computed tomography soft tissue measurements. Main Outcome Measure: Acute compartment syndrome (ACS). Results: Schatzker VI fractures (odds ratio 5.72, confidence interval 2.55–12.83, P < 0.001), high-energy mechanism (3.10, 1.26–7.58, P = 0.0096), fibular fracture (8.14, 3.33–19.96, P < 0.0001), fracture length (9.70, 2.45–37.69, P = 0.0014), and plateau-shaft combined injury (2.97, 1.15–7.70, P = 0.019) were all associated with the development of compartment syndrome. The depth of the posterior compartment was also predictive of CS (1.06, 1.02–1.09, P = 0.0025). Patients with 3 and 4 predictive markers demonstrated a 20% and 27% chance of developing ACS respectively. Conclusions: This study confirms that several factors are associated with the development of ACS. The presence of each independent predictor had a cumulative effect such that when more than one variable is present, the chance of ACS increases. This information may be used to alert providers regarding injuries that require vigilant evaluation. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.